Vsebnost ekstraktivov v skorji in lesu robinije (Robinia pseudoacacia L.) - Vek, Viljem (Acta silvae et ligni, 2019)
The content and composition of extractives in the wood and bark tissue of black locust (Robinia pseudoacacia L.) were investigated. Wood and bark samples were extracted using a Soxhlet apparatus with acetone. The extracts were gravimetrically examined to measure total hydrophilic extractive content. Total phenolic content was measured colorimetrically with a UV-Vis spectrophotometer. The wood and bark extracts were further investigated using high-pressure liquid chromatography (HPLC) to identify and quantify dihydrorobinetin in the extracts. The contents of total hydrophilic extractives, total phenols and dihydrorobinetin were higher in heartwood than in the sapwood and bark. No relationship was found between the height at which the samples were taken from the stem and the content of soluble components in the wood and bark. The heartwood of black locust represents a rich potential source of phenolic extractives.
Keywords: biorafinarije; biorefinery; black locust; dragocene spojine; ekstraktivi; extractives; HPLC; robinija; value-added compounds